Bridging the Gap - Medwin Dikwanyane Sepadi; Moshohli Kenneth Malatji; Nthabanele Enoch Rabotata; Sethuthuthu Lucky Vuma (Social Sciences and Education Research Review)
Providing school psychosocial support is essential for promoting learner well-being and academic success. However, South African schools continue to face a critical shortage of social workers, limiting access to necessary interventions for learners experiencing socio-emotional, behavioural, and mental health challenges. This literature-based study explores the role of social workers in school-based psychosocial support, the impact of their absence on learners and educators, and the broader implications for the education system. Drawing on national and international literature, the paper examines existing policies, including the Department of Basic Education Care and Support for Teaching and Learning (CSTL) framework, and highlights the gaps in implementation. The study also discusses alternative psychosocial support mechanisms currently in place and evaluates their effectiveness without dedicated social workers. Finally, the paper provides recommendations for strengthening psychosocial support structures through policy reforms, capacity building, and multi-sectoral collaboration to address the growing mental health and social challenges learners face.